Oxidation parameters determination of Cu-Al-Ni-Fe shape-memory alloy at high temperatures - Kok, Mediha; Yildiz, Koksal (Springer Heidelberg, 2014)
In this study, isothermal oxidation behavior of a Cu-Al-Ni-Fe shape-memory alloy between 500 and 900 A degrees C was investigated. Alloy samples were exposed to oxygen by TG/DTA for 1 h at a constant temperature, allowing for calculation of the oxidation constant and activation energy values of the oxidation process. The oxidation constant value increased with temperature, reaching saturation at 800 A degrees C. The effect of oxidation on crystal structure, surface morphology and chemical composition of the Cu-Al-Ni-Fe alloy was determined by X-ray diffractometer (XRD) and scanning electron microscope (SEM)-energy-dispersive X-ray (EDX) analyses. With increasing oxidation temperature, number and intensity of the characteristic 18R martensite phase peaks were reduced while Al2O3 phase peaks were increased. In parallel to the XRD results, the same variations were also detected by SEM-EDX measurements.
Keywords: Isothermal Oxidation; Behavior; Microstructure; Transformation